Analisis Profil Literasi Sains Siswa pada Materi Getaran dan Gelombang dalam Pengembangan Soal PISA Terintegrasi Mitigasi Bencana Gempa dan Tsunami - Alfarizy, Yusril; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Universitas Negeri Surabaya, 2025)
Abstract Indonesia's scientific literacy has not experienced a significant increase. Students' PISA scientific literacy scores ranged from 393 to 396 in 2000 to 2018. This is because the level of difficulty of the questions designed by teachers is not as difficult as the PISA questions and their indicators. The aim of this research is to analyze the profile of scientific literacy abilities in the PISA model which is integrated with earthquake and tsunami disaster mitigation. This research uses a quantitative approach with descriptive analysis methods. The research was conducted at a private high school in northern Surabaya on 30th October 2024. The population used in this research were 2 classes, namely XII-1 and XII-2, totaling 61 students. The sampling technique used was random sampling. The results show that the profile of scientific literacy abilities of 61 students has the criteria of 0% very high, 10% high, 24% sufficient, 10% low, and 56% very low. The average score for competence in explaining phenomena scientifically is 55, evaluating and designing scientific methods is 33, and interpreting data and evidence scientifically respectively is 39. Based on the research results, it can be concluded that students' scientific literacy profiles are very low. Keywords: Scientific Literacy Profile, PISA, Disaster Mitigation, Vibrations, Waves, Eathquake, Tsunami